Criminalistic equipment as instrument of collecting of proofs and technology of its use (Journal of actual problems of jurisprudence, 2019)
The criminalistic equipment uses various achievements of technical science and natural sciences, and also statistical and mathematical methods and many other things. As methods of criminalistic equipment various methods from area of chemistry, physics, biology, medicine and other sciences achievements in which can be useful and necessary at detection and research of traces of crimes can be used. The technical devices and subjects, scientific methods and receptions suitable for permission of the questions and tasks connected with disclosure of crimes belong to scientific and technical means of criminalist.Key words: Criminalistics, criminalistic equipment, scientific and technical methods and means, material traces of crime, participants of investigative actions, specialist criminalist.